Can U.S. multi-state climate mitigation agreements work? A perspective from embedded emission flows. (November 2022) - Song, Kaihui; Baiocchi, Giovanni; Feng, Kuishuang; Hubacek, Klaus; Sun, Laixiang; Wang, Daoping; Guan, Dabo
Highlights: There can be large carbon transfers between climate alliances of states and others. States joining climate agreements specialize in less carbon-intensive production. We discuss the challenges of extending agreements and potential carbon leakage. We discuss options that could lead to incrementally deeper sustainable cooperation. We suggest that subnational targets include embodied in the supply chain. Abstract: Subnational and non-governmental actors are expected to provide important contributions to broader climate actions. A consistent and accurate quantification of their GHG emissions is an important prerequisite for the success of such efforts. However, emissions embodied in domestic and international supply chains, that can undermine the effectiveness of climate agreements, add challenges to the quantification of emissions originating from the consumption of goods and services produced elsewhere. We examine emission transfers between the states that have joined the U.S. Climate Alliance (USCA) and others. Our results show that states pledging to curb emissions consistent with the Paris Agreement were responsible for approximately 40% of total U.S. territorial GHG emissions. However, when accounting for transferred emissions through international and interstate supply chains of the products they consume, the share of Alliance states increased to 52.4% of the national total GHG emissions. The consumption-based emissions for some Alliance states, such as Massachusetts and New York, could be more than 1.5 times higher than their production-based emissions. Our detailed sectoral analysis highlights the challenges facing such agreements to extend cooperation in the future for larger joint benefit given the potential for carbon leakage from member states implementing stricter environmental policies that could lead to higher emissions from non-member states. It is critical for these arrangements to pay close attention to transferred emissions.